(ii) Resuscitation of the adult trauma victim. Issue 6 (December 2015) - Brousil, J.; Forward, D.; Moran, C.
Abstract: The introduction of Major Trauma Networks has had a significant positive impact on the delivery of care to the seriously injured patient. Trauma is still the most common cause of death in patients under the age of 45. The hub and spoke model of the Trauma Unit – MTC has resulted in standardization of trauma care across England and the resultant improvement in patient mortality is evident in the most recent TARN data summary. Dedicated, consultant-led 'Trauma Teams' now direct the care of the critically injured from their first presentation at the emergency department. Priorities for the resuscitation of the severely injured patient follow ATLS principles, with control of massive haemorrhage given equal priority to the airway. The pre-hospital administration of tranexamic acid and intravenous antibiotics in the setting of hypovolaemic shock and open fractures represent new advances in standards of emergent care.